2005
DOI: 10.1093/rheumatology/kei029
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatologists' judgements about the efficacy of anti-TNF therapy in two neighbouring regions

Abstract: Despite the absence of overt rationing in the south of Ireland, as far as the judgement of therapeutic benefit from biologicals was concerned, the clinical judgement policies of practitioners were very similar to those in the north. The adoption of NICE/BSR guidelines in the north may have improved the uniformity of clinical practice in Northern Ireland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Kalkan and colleagues [23] found that similar factors (clinical evidence; colleagues; departmental culture; budget constraints) influenced senior rheumatologists’ prescribing decisions with biologic agents in Sweden. Kee and colleagues [24] reported that consultants in Ireland may also strategically manipulate DAS28 assessments when considering continuation of infliximab for people with RA, if symptoms were more severe than their DAS28 score indicated. Subsequent quantitative analyses of patient-level data may be subject to bias if these observations comprise inaccurate DAS28 scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kalkan and colleagues [23] found that similar factors (clinical evidence; colleagues; departmental culture; budget constraints) influenced senior rheumatologists’ prescribing decisions with biologic agents in Sweden. Kee and colleagues [24] reported that consultants in Ireland may also strategically manipulate DAS28 assessments when considering continuation of infliximab for people with RA, if symptoms were more severe than their DAS28 score indicated. Subsequent quantitative analyses of patient-level data may be subject to bias if these observations comprise inaccurate DAS28 scores.…”
Section: Discussionmentioning
confidence: 99%
“…These methods have been used extensively to understand patients’ beliefs and experiences about their own treatments and disease [2022]. Qualitative studies have been used previously to explore the influences on biologic prescribing decisions for RA in Sweden [23] and Ireland [24]. No study has used these methods to explore the factors that may influence anti-TNF prescribing decisions for RA in England; a greater understanding of this phenomenon may contribute to identifying drivers of the observed regional variation in care in the presence of uniform national recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…Similar concerns have been expressed about using the DAS28 to define the need for tumor necrosis factor inhibitors (37,38). Despite these concerns, the DAS28 is recommended for use in clinical practice in the UK (39,40) and the balance of evidence indicates its use is beneficial for routine practice (41)(42)(43).…”
mentioning
confidence: 92%